Codigestão anaeróbia de esgoto sanitário e lodo algáceo em um reator UASB - Assis, Tatiana Izato (2017)
This research aimed to study the effects of anaerobic co-digestion of domestic wastewater and algae sludge in a UASB reactor, by evaluating its performance before (phase 1) and after algal sludge recycling into the anaerobic reactor (phase 2). The UASB reactor has 3.78 m³ of useful volume and 4.8 meters in height and was monitored by 410 days. The sludge used in the anaerobic co-digestion process is a physical-chemical algae sludge without pre-treatment. After the start up that lasted 138 days, the reactor presented a satisfactory performance for the anaerobic treatment of the sewage in phase 1 (164 days) and phase 2 (108 days). The average COD concentration in the effluent was 160 mg/L and 125 mg/L for phase 1 and phase 2, respectively, while the average TSS was 48 mg/L and 41 mg/L for phase 1 and phase 2, respectively. The HTR and OLR was 8,8h and 1,14 kgCOD.m-3 .d-1 for phase 1, respectively, and 9,5h and 0,98 kgCOD.m-3 .d-1 for phase 2, respectively. The reactor sludge age decreased from 108 days (phase 1) to 98 days (phase 2) due to the sludge production increasing from 0.48 kgTS.d-1 (phase 1) to 0.57 kgTS.d-1 (phase 2). This fact implies to increase the frequency of UASB excess sludge discharge. The daily apport of algal sludge at phase 2 reduced significantly the sludge stability in the blanket region. This behavior suggests the microalgae displacement from sludge bed to sludge blanked region. The biogas production per capita was 10 L/hab.d (phase 1) and 6 L/hab.d (phase 2). The estimated methane production was 6 L/hab.d (phase 1) and 4 L/hab.d (phase 2). As a consequence, the power of the effectively captured biogas was 0.18 kW (0.0024 kW/hab) and 0.11kW (0.0015 kW/hab) in the phase 1 and 2, respectively. The decreasing on methane production at phase 2 can be attribute to the decrease of OLR and temperature. The mass balance results in terms of COD suggests that the anaerobic co-digestion process contributed to the increase of COD converted to anaerobic sludge. This relative increase in sludge production may be related to the non-digestion of the microalgae which are captured by the sludge from the reactor but are not fully digested by it. It was concluded that in order to increase the conversion of the organic material of the reactor, the UASB must be operated at the maximum sludge age and it’s necessary pre-treat the algal sludge before the anaerobic co-digestion.